The Effect of Financial Access, Financial Literacy and Financial Experience on MSME Financial Behavior - Parulian Parulian; Emmelia Tan (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
MSMEs contribute 60.6% to the Gross Domestic Product (GDP) in Indonesia. However, on the other hand, the level of financial literacy and financial experience of MSME actors is still low, as well as the lack of access to financial institutions for this sector. The purpose of this study is to determine whether there is an effect of financial access (X1), financial literacy (X2) and financial experience (X3) on the financial behavior (Y) of SMEs. The research data was tested using SPSS version 25, with the results of the study both partially using the T test and simultaneously using the F test there was a significant influence between the variables of financial access (X1), financial literacy (X2) and financial experience (X3) on financial behavior (X1) Y), the coefficient of determination in Adjusted R Square explains the magnitude of the influence of 72.8%, while the remaining 27.2% is influenced by other factors.